Kinetics and mechanism of the iron phthalocyanine catalyzed reduction of nitrite by dithionite and sulfoxylate in aqueous solution - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2005)
The reactions of sodium nitrite with sodium dithionite and sulfoxylate ion were studied in the presence of iron(III) tetrasulfophthalocyanine, Fe (TSPc), in aqueous alkaline solution. Kinetic parameters for the different reaction steps in the catalytic reduction by dithionite were determined. The final product of the reaction was found to be nitrous oxide. Contrary to this, the product of the catalytic reduction of nitrite by sulfoxylate was found to be ammonia. The striking difference in the reaction products is accounted for in terms of different structures of the intermediate complexes formed during the reduction by dithionite and sulfoxylate, in which nitrite is suggested to coordinate to the iron complex via nitrogen and oxygen, respectively. Sulfoxylate is shown to be a convenient reductant for the synthesis of the highly reduced iron phthalocyanine species Fe(TSPc) in aqueous solution. The kinetics of the reduction of Fe(TSPc) to Fe (TSPc), as well as the oxidation of the latter species by nitrite, was studied in detail. © 2005 American Chemical Society.